Rekonstruksi Citra Perusahaan Melalui Komunikasi TJSL: Studi Kasus Strategi Humasda PT KAI Daop 3 Cirebon - Veranika Aulia Agatha; Anggun Anindya Sekarningrum (MUKASI: Jurnal Ilmu Komunikasi, 2026)
Public Relations strategies play an important role in communicating corporate social responsibility as an effort to build a corporate image. This study adopts a constructivist paradigm using a qualitative approach with a case study method. Data were collected through in-depth interviews with the regional Public Relations unit and beneficiary communities, supported by documentation such as activity reports, press releases, and media publications. The findings indicate that the communication strategy was implemented in a structured manner through stages of research and planning, program implementation, communication publication, and evaluation. TJSL Communication was carried out through direct interaction with the community, mass media, and the company’s social media platforms. A humanistic and contextual communication approach enabled the TJSL program to be perceived not merely as the distribution of assistance, but as an expression of corporate care and social commitment. This approach contributed to the formation of a positive image of PT KAI Daop 3 Cirebon as a company that is socially responsible, transparent, and committed to sustainable social and environmental development.